PERFORMANCE OF JAPANESE QUAIL ON DIFFERENT MANAGEMENT SYSTEM (Indian Journal of Animal Production and Management, 2023)
This study was conducted to investigate the effect of two management system; deep litter and cage system on performance of Japanese quail, as management plays an importanat role in growth, carcass quality in terms of yield and nutritional composition as well as laying performance. Two hundred Japanese quail of two weeks old were selected randomly and divided into two groups with two replicates of hundred quails in each with male and female ratio of 1:1 and housed in cages and deep litter system. Body weights, carcass yield, dressing percentage, egg production were recorded during the experimental period. The results revealed significant difference (p
Keywords: Japanese quail; deep litter system and cage system